2008
DOI: 10.2174/1874241600801010092
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Damage and Antioxidant Status in Diabetes Mellitus and Rheumatoid Arthritis: A Comparative Study

Abstract: The present work compares and correlates antioxidant defenses and oxidative stress markers in patients with Diabetes Mellitus (DM) and in those with Rheumatoid Arthritis (RA) in order to find out if new evidences for a possible relationship between these pathologies can be found. Stress markers and antioxidant defenses were tested in blood samples from RA, Type I and Type II DM patients. Erythrocytes (RBC) showed increased susceptibility to lipid peroxidation in both DM and RA, whereas basal oxidation was high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
(57 reference statements)
1
6
0
Order By: Relevance
“…MDA mainly formed due to lipid peroxidation and increases ROS generation. GSH play a crucial role as a scavenger of ROS and hinders oxidative stress 33 . Our findings supported an anti-inflammatory role of CCHE as indicated by the decrease in MDA levels and increase in GSH levels in rats with formaldehyde-induced arthritis, in line with a previous study by Liao et al 6 Some studies have reported that ROS plays a role of sending a stimulatory signal for NF-κB activation that further induced the expression of pro-inflammatory cytokine 34 .…”
Section: Discussionsupporting
confidence: 91%
“…MDA mainly formed due to lipid peroxidation and increases ROS generation. GSH play a crucial role as a scavenger of ROS and hinders oxidative stress 33 . Our findings supported an anti-inflammatory role of CCHE as indicated by the decrease in MDA levels and increase in GSH levels in rats with formaldehyde-induced arthritis, in line with a previous study by Liao et al 6 Some studies have reported that ROS plays a role of sending a stimulatory signal for NF-κB activation that further induced the expression of pro-inflammatory cytokine 34 .…”
Section: Discussionsupporting
confidence: 91%
“…Mechanisms of hyperglycemia induced production of oxygen free radicals: Hyperglycemia is known to cause elevation in plasma free radical concentrations (Hammes et al, 1997;Cimato et al, 2008). The production of free radicals is engendered by uncontrolled hyperglycemia, which may occur via several routes (Rolo and Palmeira, 2006;Giacco et al, 2010;Bajaj and Khan, 2012): (1) increased glycolysis (Vaag et al, 1992), (2) intercellular activation of sorbitol (polyol) pathway (Williamson et al, 1993;Di Naso et al, 2011), (3) autoxidation of glucose (Wolff et al, 1991), (4) protein kinase C (PKC) dependent activation of NAD(P)H oxidase (Inoguchi et al, 2003), (5) increased hexosamine pathway flux (Rolo and Palmeira, 2006), 6increased intracellular formation of AGEs (Giacco et al, 2010), 7increased expression of receptor for AGEs and its activating ligands (Giacco et al, 2010) and 8non-enzymatic protein glycation (Ceriello et al, 1992).…”
Section: Oxidative Damage and Modification Of Macromolecules: The Radmentioning
confidence: 99%
“…Importantly, even pre-DM individuals showed elevated 8-hydroxyguanosine, which suggested that oxidative damage to DNA is present even before the clinical development of DM (Styskal et al, 2012). Recently, raised level of oxidative stress was also demonstrated in the obese as reflected in increased lipid peroxidation, protein carbonylation and ortho-tyrosine and meta-tyrosine formation in DM individuals (Keaney and Loscalzo, 1999;Cumaoglu et al, 2007;Cimato et al, 2008;Chis et al, 2009;Styskal et al, 2012). However, the levels of these oxidative stress indicators, as well as generation of ROS by leucocytes, were reversed following restriction to 1,000 calories/day for 4 weeks (Dandona et al, 2001).…”
Section: Fig 1: Relationship Between Rates Of Oxidant Generation Anmentioning
confidence: 99%
“… 10 , 11 , 12 , 13 , 14 Most of these plants contain phytochemicals that possess antioxidant properties, which could help overcome oxidative stress associated with the diabetic state. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%